1943
DOI: 10.1111/j.1744-7348.1943.tb06169.x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of the fungus Rhizoctonia solani Kiihn in the soil

Abstract: Rhigoctaia so&& was found able to grow 0s a saprophyte through natural unsterilized soil. Its rate of growth under different soil conditions in glass tumblers was studied by the Rossi-Cholodny soil-plate method. Growth was most rapid at the lowest soil-moisture content tested, viz. 30 yo saturation, and was accelerated by for& aeration of the soil. The maximum distance to which mycelial growth could be suppofied on the food reserves of the agar inoculum alone was some 5 ~n . , as shown by extent of growth thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0

Year Published

1959
1959
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(38 citation statements)
references
References 11 publications
2
36
0
Order By: Relevance
“…Bars represent standard errors of the mean of three replicates. {b) Tbe saprophytic growth of Rhizoctonia solani in a sandy loam soil (Woburn) from Blair (1943); symbols represent five isolates. Growth of isolates was assessed by the Rossi-Gholodny method and shows the mean growth of hyphae on 12 slides buried in the soil for 5 d. The moisture contents of tbe original data were converted to kPa from a moisture characteristic curve of this soil (data not shown), assuming the characteristics not to have changed.…”
Section: Figure 2 (C) the Saprophytic Growth Of The Fungusmentioning
confidence: 99%
See 3 more Smart Citations
“…Bars represent standard errors of the mean of three replicates. {b) Tbe saprophytic growth of Rhizoctonia solani in a sandy loam soil (Woburn) from Blair (1943); symbols represent five isolates. Growth of isolates was assessed by the Rossi-Gholodny method and shows the mean growth of hyphae on 12 slides buried in the soil for 5 d. The moisture contents of tbe original data were converted to kPa from a moisture characteristic curve of this soil (data not shown), assuming the characteristics not to have changed.…”
Section: Figure 2 (C) the Saprophytic Growth Of The Fungusmentioning
confidence: 99%
“…These results are preliminary and much work still needs to be done on the analysis of these regions m field soiL (a) Figure 9. Heterogeneity of the regions of favourable and unfavourable sites for the saprophytic growth of R. solani around radish based on the data of Blair (1943). The two-dimensional representations are of the volumetric water contents (cm^ water cm"^ soil) in a 50 x 50 ROI around single roots of 8-d-old radish seedlings observed under ' drier' conditions (-10 kPa) at depths of (o) 15 nim and (6) 3 5 mm and ' wetter^ conditions (-4 kPa) at depths of (c) 1 5 mm and {d) 3 5 mm; tbe y-axis is volumetric water content (cm^ cm'').…”
Section: Fungal Growth In Soil Of Heterogeneous Zvater Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…causing stem rot of Dianthus caryophyllus was above 88°F and at soil mois tures unsuitable for best derelopraent of the plsj^t, Blair (1943) found that H. solani grew fastest at 30 per cent saturation which was the lovrest soil moisture content tested. Papavizas and Davey (1961) observed the saprophytic activity of Rhizoctonia sp.…”
Section: Effect Of M Hapla On Yield Of Alfalfamentioning
confidence: 99%